ChemInform Abstract: Synthesis, Structure, Magnetism, and Optical Properties of Cs2Cu3DyTe4. Issue 7 (22nd February 2013) - Babo, Jean‐Marie; Choi, Eun Sang; Albrecht‐Schmitt, Thomas E.
Abstract The title compound is prepared by reaction of Dy, Cu, Te, and CsN3 (evacuated silica tube, 850 °C, 5 d).